Optimization of Fe Leaching Method for Indonesia Laterite Rocks using Experiment Design Central Composite Design (CCD)-Response Surface Methodology (RSM) - Alifah Hernanda, Rasikha; Fakhri Izzul Haq, Muhammad; Suprapto, Suprapto; Lailun Ni’mah, Yatim (Indonesian Journal of Chemical Analysis (IJCA), 2025)
This study's goal is to maximize the soil's iron revocation process by exploiting the CCD (Central Composite Design) and RSM (Response Surface Method) experimental designs. Kendari, Kolaka, and Southeast Sulawesi are the laterite rocks used in this study. XRF testing is used to identify the mineral components contained in laterite rocks. The iron content of the laterite rocks is 68.90% according to XRF analysis, and the remaining metal content needs to be separated by leaching. Variations in the S/L ratio, leaching time, and leaching temperature were used in the leaching process, and these changes had an impact on the amount of extracted iron. Atomic Absorbtion Spectroscopy (AAS) is used to assess the leaching process results and quantify the iron concentration. Using CCD-RSM to optimize process settings, ideal conditions are achieved at a 1:1 S/L ratio, a 90-minute leaching period, 80°C, and a 19.20% iron extraction concentration. As a result, this study not only increases the iron's efficiency but also offers a technique that may be used to extract additional metals from lateritic rocks or comparable materials.